Comparison of Ru/La2O2CO3 performance in two different membranereactors for hydrogen production - Faroldi, Betina María Cecilia (2013)
Ruthenium catalysts supported on a lanthanum oxycarbonate phase (La2O2CO3) with high surface area were prepared. All solids were stable for at least 90 h on stream in the combined dry reforming and oxidation of methane reactions. The catalyst with more stable metallic Ru species was selected to be studied under the more severe conditions of membrane reactors. A double tubular membrane reactor was built using a commercial self-standing membrane or a composite Pd/NaAPSS membrane. The Pd membrane reactor exhibited a higher H2 permeated/CH4 fed ratio at 450 ◦C that could be related to its higher hydrogen permeability. The comparison of the catalytic behavior of Ru catalysts supported on high surface area lanthanum oxycarbonate and La2O3–SiO2 binary support in a membrane reactor was performed at 550 ◦C. On the retentate side, the molar composition of CO2 was similar to that of CH4 when the Ru/La2O2CO3 catalyst was employed, which suggests that this solid did not favor the RWGS reaction under DRM conditions producing a higher H2 permeated/CH4 fed ratio. The Ru catalysts showed a similar performance to that of our best Rh solids when the fractions of the reaction equilibration and H2 permeated/(CH4 fed × permeation area) ratio were compared.